La manzanita podridita (2022)
The foundations of the research are social criticism that starts from the feeling of indignation at facts of the ignored daily context, and the second axis is sarcasm as a valid means of artistic expression to raise axes of critical thought. In turn, the axes are linked from the treatment of the image in the audiovisual media, suggesting that the work has the capacity for massive propagation and resonance. Even the possible sequels left by the project due to the variety of its format and the axes of reflection that are addressed.